SYUBHAT MILIK (Studi Tentang Pergantian Benen di Bengkel Tambal Ban Di Nagari Limo Kaum) - Ridho Rizky Putra; Yustiloviani Yustiloviani (Institut Agama Islam Negeri Batusangkar, 2023)
This study examines ownership benen former left by the vehicle owner in a tire repairs. The problem is implementation of the contract and ownership benen former left by vehicle in a tire repairs. From the problems appear question how to implementation of the contract and ownership benen former left by the vehicle owner in a tire repairs. This study is a field research. This data obtained through observation result and interview with the workshop owner and the vehicle owner. After the data is collected processed by analysis qualitative descriptive technique. The result discussed with theory stated. This research found that there is a lack of clarity in the implementation of the contract clear between the workshop owner with the vehicle owner and ownership the benen former is right of ownership from the vehicle owner.